Unraveling the personality traits of civil heroes in great disaster: a qualitative study - Hu, Haili; Ou, Dan (Frontiers in Psychology, 2025)
IntroductionHeroes are everywhere, and shine the brightest in the dark. Although the concept of heroism has been widely discussed in the fields of philosophy and social sciences, the personality traits of civil heroes emerging from great disasters has remained unexplored topic.MethodsThe qualitative research methodologies are conducted to dissect and elucidate the multifaceted personality traits of civil heroes, through semi-structured interviews with 50 eyewitnesses and participants in relief efforts following the Wenchuan Earthquake of China.ResultsCivil heroes are ordinary individuals who display profound loyalty to the nation and its people, uphold a steadfast belief in self-reliance, boldly confront risks and challenges, continually surpass themselves, and strive to accomplish remarkable feats. The personality traits encompass five dimensions (i.e., patriotism and love for the people, independence and self-improvement, relentless striving and perseverance, selflessness and fearlessness, and grounded in facts and innovation), which intricately intertwine and collectively shape the luminous image of civil heroes, serving as a potent catalyst for social progress and civilization.DiscussionThe research augments the theoretical framework and provides a more comprehensive and nuanced understanding of civil heroes, inspiring more individuals to dedicate themselves to societal welfare and foster a more harmonious and beautiful society.